1967
DOI: 10.1203/00006450-196701000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Aspects of Blood Coagulation in the Generalized Shwartzman Reaction: 1. Effects of Variation of Preparative and Provocative Doses of E. Coli Endotoxin

Abstract: The generalized Shwartzman reaction (GSR) is induced in rabbits by two properly spaced intravenous injections of bacterial endotoxin and is characterized by the occurrence of bilateral renal cortical necrosis. This report describes the quantitative changes in the coagulation mechanism in response to variation of preparative and provocative doses of E. coli endotoxin and of the interval between injections. It also correlates the coagulation changes with the pathologic findings of renal cortical necrosis.Renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Several investigators have reported data showing that the fibrinogen level in other species also doesn't change for some hours after endotoxin injections. Rabbits given relatively heavy doses of endotoxin intravenously have no change in the fibrinogen level for over 6 hr, but it is increased twofold by 24 hr (3,4,14,15). In humans, intramuscular injection of typhoid vaccine (1) or of en-dotoxin (16) caused a slight drop in the fibrinogen level during the first few hours, followed by an increase starting after the 12th but before the 24th hour.…”
mentioning
confidence: 98%
“…Several investigators have reported data showing that the fibrinogen level in other species also doesn't change for some hours after endotoxin injections. Rabbits given relatively heavy doses of endotoxin intravenously have no change in the fibrinogen level for over 6 hr, but it is increased twofold by 24 hr (3,4,14,15). In humans, intramuscular injection of typhoid vaccine (1) or of en-dotoxin (16) caused a slight drop in the fibrinogen level during the first few hours, followed by an increase starting after the 12th but before the 24th hour.…”
mentioning
confidence: 98%
“…The generalized Shwartzman reaction was produced in the classical manner (5). Animals received two intravenous injections of endotoxin (0.1 mg/kg) 24 hr apart.…”
mentioning
confidence: 99%
“…It is now widely accepted that the generalized Shwartzman reaction (GSR) results from induction of intravascular coagulation (McKay, and Shapiro, 1958 ;Kleinmaier, Goergen, Lasch, Krecke and Bohle, 1959;Rodriguez-Erdmann, 1964;Hjort and Rapaport, 1965 ;Corrigan, Abildgaard, Vanderheiden and Schulman, 1967). As classically produced, the reaction requires intravenous injection of two doses of endotoxin administered at least 6 hours apart with the optimum interval being 12-24 hours (Thomas and Good, 1952).…”
mentioning
confidence: 99%
“…As classically produced, the reaction requires intravenous injection of two doses of endotoxin administered at least 6 hours apart with the optimum interval being 12-24 hours (Thomas and Good, 1952). Studies on the role of each injection have indicated that although the initial (preparative) injection activates the coagulation mechanism to a slight degree its major effect is to impair the function of the reticuloendothelial system (RES) (Benacerraf and Sebestyen, 1957;Lee, 1962;Levin and Beck, 1966;Corrigan et al, 1967). The second (provocative) dose of endotoxin is then cleared less efficiently as are the intermediates of the coagulation process and fibrin itself.…”
mentioning
confidence: 99%
See 1 more Smart Citation